Increased Responses of Phenoloxidase in Chlorantraniliprole Resistance of Plutella xylostella (Lepidoptera: Plutellidae). Issue 4 (3rd July 2020) - Wang, Nian-Meng; Li, Jing-Jing; Shang, Ze-Yu; Yu, Qi-Tong; Xue, Chao-Bin
Abstract: The diamondback moth ( Plutella xylostella, DBM) is an important pest of cruciferous vegetables. The use of chlorantraniliprole has been essential in the management of the DBM. However, in many countries and areas, DBM has become highly resistant to chlorantraniliprole. Three different DBM strains, susceptible (S), chlorantraniliprole-selected (Rc ), and field-collected (Rb ) resistant strains/populations were studied for the role of phenoloxidase in resistance development to the insecticide. By assaying the activity of phenoloxidase (PO) in the three different DBM strains, the results showed that the PO activity in the Rc strain was increased significantly compared with the S strain. The synergistic effects of quercetin showed that the resistant ratio (RR) of the QRc larvae to chlorantraniliprole was decreased from 423.95 to 316.42-fold compared with the Rc larvae. Further studies demonstrated that the transcriptional and translational expression levels of PxPPO1 ( P. xylostella prophenoloxidase-1 gene) and PxPPO2 ( P. xylostella prophenoloxidase-2 gene) were increased to varying degrees compared with the S strain, such as the transcriptional expression levels of PxPPO2 were 24.02-fold that of the S strain. The responses of phenoloxidase were significantly different in chlorantraniliprole-resistant DBM. Graphical Abstract: